An observational study of left ventricular hypertrophy and left axis deviation in ECG among type 2 diabetic patients with and without hypertension from a rural hospital in Karnataka - Sindhu B R; Shashikantha Shashikantha (Journal of Clinical and Biomedical Sciences)
Introduction: Type 2 diabetes mellitus is rampant around us. Diabetes and hypertension go hand in hand when it comes to non-communicable diseases and diabetes per se leads to hypertension and together they in-crease cardiovascular diseases. This increases morbidity and mortality in diabetic patients. Assessing ECG in rural health settings would help us to decrease the cardiovascular morbidity by initiating appropriate treat-ment. AIM: To study the age and gender of type 2 diabetic patients with and without hypertension and to compare LVH, LAD among 2 groups. Material and Methods: 97 diabetics attending OPD and IPD from Nov 2015- May 2017 were grouped into 2. Group I of 50 were hypertensive diabetics and group II of 47 were normotensive diabetics. Detailed history was noted and relevant investigations were done. Result: Among the 97 diabetics, mean age in the group I was 62±10.76yrs and in group II was 62±9.44 yrs. Fe-males outnumbered males among the hypertensive diabetics (group I) and males were more among the normo-tensive diabetics (group II). In group I, maximum percentage (26%) was diabetic from 6-10yrs and 20% pa-tients were newly detected diabetics. In group II, 27.7% were newly detected, 25.5% diabetic from 6-10yrs. Pulse rate, systolic blood pressure and diastolic blood pressure were higher in group I compared to group II and it is statistically significant with P value 0.003, <0.001 and <0.001 respectively. Conclusion: Majority was among the age group of 51-70yrs and majority were females in hypertensive diabetic groups. Maximum number of patients had LVH finding in hypertensive diabetics (22%) in ECG. Large number of studies should be conducted to understand the disease and variation in its risk factors in India. Keywords: Hypertension, type 2 diabetes mellitus ,ECG, Left Ventricular Hypertrophy.